Realization of III–V Semiconductor Periodic Nanostructures by Laser Direct Writing Technique - Huang, Yuan-qing (Nanoscale Res Lett, 2017)
In this paper, we demonstrated the fabrication of one-dimensional (1D) and two-dimensional (2D) periodic nanostructures on III–V GaAs substrates utilizing laser direct writing (LDW) technique. Metal thin films (Ti) and phase change materials (Ge(2)Sb(2)Te(5) (GST) and Ge(2)Sb(1.8)Bi(0.2)Te(5) (GSBT)) were chosen as photoresists to achieve small feature sizes of semiconductor nanostructures. A minimum feature size of about 50 nm about a quarter of the optical diffraction limit was obtained on the photoresists, and 1D III–V semiconductor nanolines with a minimum width of 150 nm were successfully acquired on the GaAs substrate which was smaller than the best results acquired on Si substrate ever reported. 2D nanosquare holes were fabricated as well by using Ti thin film as the photoresist, with a side width of about 200 nm, but the square holes changed to a rectangle shape when GST or GSBT was employed as the photoresist, which mainly resulted from the interaction of two cross-temperature fields induced by two scanning laser beams. The interacting mechanism of different photoresists in preparing periodic nanostructures with the LDW technique was discussed in detail.